Platelet lysates-based hydrogels incorporating bioactive mesoporous silica nanoparticles for stem cell osteogenic differentiation. (January 2021) - Tavares, M.T.; Santos, S.C.; Custódio, C.A.; Farinha, J.P.S.; Baleizão, C.; Mano, J.F.
Abstract: Scaffolds for bone tissue regeneration should provide the right cues for stem cell adhesion and proliferation, but also lead to their osteogenic differentiation. Hydrogels of modified platelet lysates (PLMA) show the proper mechanical stability for cell encapsulation and contain essential bioactive molecules required for cell maintenance. We prepared a novel PLMA-based nanocomposite for bone repair and regeneration capable of releasing biofactors to induce osteogenic differentiation. Human bone marrow-derived mesenchymal stem cells (hBM-MSCs) were encapsulated in PLMA hydrogels containing bioactive mesoporous silica nanoparticles previously loaded with dexamethasone and functionalized with calcium and phosphate ions. After 21 d of culture, hBM-MSCs remained viable, presented a stretched morphology, and showed signs of osteogenic differentiation, namely the presence of significant amounts of alkaline phosphatase, bone morphogenic protein-2 and osteopontin, hydroxyapatite, and calcium nodules. Developed for the first time, PLMA/MSNCaPDex nanocomposites were able to guide the differentiation of hBM-MSCs without any other osteogenic supplementation. Graphical abstract: A brand-new platelet-lysate based hydrogel containing bioactive nanoparticles shows osteogenic properties able to differentiate stem cells without further osteogenic supplementation. Image 1